Surveillance of mosquito vectors in Southern Sweden for Flaviviruses and Sindbis virus. Issue 1 (1st January 2019) - Hesson, Jenny C.; Lundin, Emma; Lundkvist, Åke; Lundström, Jan O.
ABSTRACT: There are three human pathogenic bird-viruses transmitted by Culex mosquitoes in Europe: the alphavirus Sindbis and the flaviviruses West Nile virus and Usutu virus. Cases of Sindbis fever occur in the north while the flaviviruses are reported from southern Europe. In this study, 7933 Culex pipiens/torrentium mosquitoes from southern Sweden were screened by RTqPCR for these viruses. None of the mosquitoes were positive for viral RNA. The importance of mosquito species composition is discussed as a potential explanation to the lack of detection of mosquito-borne viruses in southern Sweden. However, continued surveillance of mosquitoes for Flaviviruses would be valuable as an early warning for public health awareness.